Enhanced airways responsiveness in rats depleted of sensory neuropeptides by neonatal capsaicin treatment - Medeiros, M. V.; De Luca, IMS; Bricola, AAO; Zanesco, A.; De Nucci, G.; Antunes, E. (Elsevier B.V., 2003)
This study aimed to investigate the in vivo and in vitro reactivity of airway smooth muscle in rats depleted of sensory neuropeptides by treatment with capsaicin at neonatal stage. Wistar rats were neonatally injected with either capsaicin (50 mg/kg, s.c., 2nd day of life) or its vehicle (10% ethanol and 10% Tween 80, in 0.9% w/v NaCl solution) and used at adult ages (60-70 days later). Analysis of the lungs showed a higher number of infiltrating neutrophils, eosinophils and mononuclear cells into the peribronchiolar regions of capsaicin-pretreated rats compared to vehicle group. This was associated with a higher contraction index of bronchiolar wall in the capsaicin group. The in vitro tracheal reactivity in response to methacholine (full muscarinic agonist) and pilocarpine (partial muscarinic agonist) was also significantly higher in capsaicin-pretreated rats compared to vehicle group. In conclusion, the neuropeptide depletion by capsaicin neonatal treatment lead to marked contraction of the rat airways at adult age, suggesting a protective role for C fibers in the lungs. (C) 2003 Elsevier B.V. Ireland Ltd. All rights reserved.
Keywords: non-adrenergic non-cholinergic fibers; lung; muscarinic receptors; capsaicin